Microscopic observation of `Gaharu` wood from Aquilaria malaccensis - Mohamed, Rozi; Wong, Mun Theng; Halis, Rasmina (Universiti Putra Malaysia Press, 2013)
Aquilaria produces fragrant wood known as `Gaharu` in its stem and branches, often in mature and damaged trees. In this study, anatomical characteristics in juvenile and mature trees were investigated by comparing their anatomical structures after various staining methods and direct observations under a light microscope. Juvenile and mature wood share similar anatomical structures. No major differences were observed other than the percentage of area covered by included phloem in juvenile was 2.16 times more than that of the mature wood. Microscopic observation revealed that in mature resinous wood, brownish bodies were found in ray and axial parenchyma, included phloem, xylem vessels and fibres, and this finding indicates that these are important elements for `Gaharu` depositing. Thus, it was concluded that juvenile tree possess the anatomical features of that of mature wood in producing `Gaharu`.